Addressing Alumni Data Challenges in Vocational Education Through Web-Based Information System Development - Melda Triyana Tanjung; Denny Kurniadi; Legiman Slamet; Ahmaddul Hadi (Jurnal Vokasi Teknik Informatika, 2025)
The lack of centralized and accurate alumni data management systems remains a challenge for many vocational schools. This study aims to develop a web-based alumni information system for SMK Negeri 1 Koto XI Tarusan to streamline alumni data processing and improve post-graduation engagement. Using the Waterfall development model, the system was designed through sequential stages including requirement analysis, system design, implementation, testing, and maintenance. The result is a role-based information system that includes separate dashboards for administrators, alumni, and alumni coordinators. The system allows secure login, data editing, event announcements, and alumni networking. The implementation demonstrates that a structured development model can effectively address institutional data management needs and enhance user interaction. However, future improvements are needed to support mobile access, analytics integration, and broader deployment across institutions. This system serves as a foundational step toward digital transformation in alumni management for vocational education institutions.